In the shadow of wind energy: Predicting community exposure and annoyance to wind turbine shadow flicker in the United States. (May 2022) - Haac, Ryan; Darlow, Ryan; Kaliski, Ken; Rand, Joseph; Hoen, Ben
Abstract: The moving shadows caused by wind turbines, referred to as "shadow flicker" ("SF"), are known to generate annoyance in a subset of the exposed population. However, the relationship between the level of modeled SF exposure and the population's perceived SF and SF annoyance is poorly understood. Improved understanding of SF exposure impacts could provide a basis for exposure thresholds and, in turn, potentially improve community acceptance of and experience with wind power projects. This study modeled SF exposure at nearly 35, 000 residences across 61 wind projects in the United States, 747 of which were also survey respondents. Using these results, we analyzed the factors that led to perceived SF and self-reported SF annoyance. We found that perceived SF is primarily an objective response to SF exposure, distance to the closest turbine, and whether the respondent moved in after the wind project was built. Conversely, SF annoyance was not significantly correlated with SF exposure. Rather, SF annoyance is primarily a subjective response to wind turbine aesthetics, annoyance to other anthropogenic sounds, level of education, and age of the respondent. We also examined regulations governing SF in the sample project areas and compared them to SF exposure in the surrounding population. Additionally, we found that noise limits could serve as a proxy for SF exposure, as 90% of those exposed to wind turbine sound of no more than 45 dBA L1h had SF exposure of less than 8 h per year (a prototypical EU regulatory threshold). Highlights: Shadow flicker (SF) was modeled at 35, 000 residences sorrounding US wind turbines, including 747 survey respondent homes More than 50% of homes within 500 m of the nearest turbines had some modeled SF. Modeled SF exposure strongly predicted if a respondent perceived SF in their home Higher modeled SF exposure levels did not lead to higher levels of self-reported annoyance to SF. Instead, self-reported SF annoyance was correlated with subjective factors, e.g., project appearance and general annoyance